Negosiasi Identitas Etnis Lampung dalam Upaya Mempertahankan Bahasa Lampung sebagai Identitas Budaya - Afri Setya, Rega; Rahardjo, Turnomo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
Bahasa Lampung as a cultural identity is facing the threat of extinction which is marked by the infrequent use of the language in its own land, that is Lampung Province. The use of Bahasa Lampung was cut off in the older generation, while the younger generations have begun to leave the use of Bahasa Lampung. In addition, the cultural heterogeneity that exists in Lampung Province makes the use of Bahasa Indonesia becomes a solution so the communications among different ethnics may happen. This has made the use of the national language increases, while the use of Bahasa Lampung is abandoned. However, in the midst of the extinction threat to Bahasa Lampung, there are areas such as Pardasuka that still maintain the use of Bahasa Lampung. The use of Bahasa Lampung is maintained by children and adults.This study aims to describe the identity negotiation of Lampungese ethnic in the effort of maintaining Bahasa Lampung as a cultural identity. This study also aims to describe the perceptions of the non-Lampung ethnic community about the identity negotiation of Lampungese Ethnic in the effort of maintaining Bahasa Lampung as a cultural identity. This study is a qualitative research that uses a constructivism paradigm with a phenomenological approach. The theory used in this research is the Identity Negotiation Theory by Stella Ting-Toomey. The results of this study were obtained through in-depth interviews to 6 informants, consisting of 3 Lampungese ethnic informants and 3 non-Lampung ethnic informants. In addition, the research results were also obtained from direct observation activities conducted by researcher at the research location, which is Pardasuka.The results showed that the identity negotiation of Lampungese Ethnic is carried out in four forms. First, the formation of identity in the family environment carried out by parents to their children. Second, the application of social punishment in the community by giving some humiliations and an exclusion for anyone who leaves the use of Bahasa Lampung. Third, the application of symbolic efforts, such as giving cultural titles and using Bahasa Lampung as signs in public facilities. Fourth, organizing cultural themed events which display literatures of Bahasa Lampung such as rhymes and poetry. On the other hand, the non-Lampung ethnic groups as immigrants show several forms of response to the efforts of Identity Negotiation of Lampungese Ethnic as an accommodation effort. One of the efforts is done by doing an assimilation to accept all Lampungese cultural identities, especially Bahasa Lampung and eliminating the identity of their origin ethnic. In addition, some of the immigrants also carry out an acculturation effort by obtaining some aspects of cultural identity, especially Bahasa Lampung without eliminating the identity of their origin ethnic. In the assimilation and acculturation efforts, non-Lampungese ethnics as migrants try to mingle with Lampungese ethnic society to acquire Bahasa Lampung as a cultural identity.